Idealism, Pragmatism, and the Birth of Pragmatist Educational Thought in America - James Scott Johnston (Cadernos de História da Educação)
This article articulates some of the historic as well as the main philosophic contributions to the transitional period in educational thought in America, 1866-1895. This is a period in which the movement away from idealism towards pragmatism as the basis for educational thought began. Contemporaneous with the development of pragmatism was a development in educational thought that stressed naturalism, functionalism, and the organic nature of mind and behaviour. As idealism laid claim to the dominant philosophy in America in the period 1866-1895, so too did it lay claim to being the dominant philosophic presupposition of educational thought. It was the first American philosophy of education: America’s first philosophy of education was not pragmatist; it was idealist, though this would change, beginning in the mid-1890’s. As pragmatism began to take hold of philosophy at the fin de siècle, so too did it begin to take hold of, and later dominate, the philosophic presuppositions of educational thought.